Hypothetical and factual willingness to participate in biobank research (European Journal of Human Genetics, 2011)
Abstract In the debate on biobank regulation, arguments often draw upon findings in surveys on public attitudes. Surveys on willingness to participate in research may not always predict actual participation rates, however. We compared hypothetical willingness as estimated in eleven surveys conducted in Sweden, Iceland, UK, Ireland, US, and Singapore to factual participation rates in twelve biobank studies. Studies were matched by country and approximate time frame. Of 22 pairwise comparisons, twelve suggest that factual willingness to participate in biobank research is greater than hypothetical, six indicate the converse relationship, and four are inconclusive. Factual donors, in particular when recruited in health care or otherwise face-to-face with the researcher, are possibly motivated by factors that are less influential in a hypothetical context, such as altruism, trust, and sense of duty. The value of surveys in assessing factual willingness may thus be limited. linus.johnsson@crb.uu.se (Johnsson, Linus) Uppsala University - Box 564, Uppsala, Sweden SE-751 22--> - SWEDEN (Johnsson, Linus) Uppsala University - Box 564, Uppsala, Sweden SE-751 22--> - SWEDEN (Helgesson, Gert) Uppsala University - Box 564, Uppsala, Sweden SE-751 22--> - SWEDEN (Rafnar, Thorunn) Uppsala University - Box 564, Uppsala, Sweden SE-751 22--> - SWEDEN (Halldorsdottir, Ingibjorg) Uppsala University - Box 564, Uppsala, Sweden SE-751 22--> - SWEDEN (Kee-Seng, Chia) Uppsala University - Box 564, Uppsala, Sweden SE-751 22--> - SWEDEN (Eriksson, Stefan) Uppsala University - Box 564, Uppsala, Sweden SE-751 22--> - SWEDEN (Hansson, Mats G.) SWEDEN Accepted: 2010-06-09 Received: 2010-01-20 Revised: 2010-06-07